HUBUNGAN PERILAKU MEROKOK DENGAN PRESTASI BELAJAR PADA MAHASISWA PROGRAM STUDI ILMU KEPERAWATAN UNIVERSITAS RIAU - Rina ' Yuliarti; Darwin ' Karim; Febriana Sabrian ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2015)
Abstract The aim of this research is to identity the relationship of smoking behavior and academic achievement of nursing students in University of Riau. This research used a descriptive correlative design. This research was conducted on 60 male students in school of nursing University of Riau by using total sampling technique. Measuring instrument used was a questionnaire. The analysis used univariate and bivariate analysis with one-way Anova test. The results showed that there is a relationship between smoking behavior and academic achievement of nursing students in University of Riau with p value of 0.042, where p value < α (p value < 0,05). It is recommended for student not to smoke because smoking behavior has negative impact to physical health and cognitive function. Moreover, it can affect the health of the people around. Keywords: smoking behavior, academic achievement